Synergistic antibacterial effect of silver and ebselen against multidrug‐resistant Gram‐negative bacterial infections - Lili Zou; Jun Lu; Jun Wang; Xiaoyuan Ren; Lanlan Zhang; Yu Gao; Martin E Rottenberg; Arne Holmgren (EMBO Molecular Medicine)
Abstract Multidrug‐resistant (MDR) Gram‐negative bacteria account for a majority of fatal infections, and development of new antibiotic principles and drugs is therefore of outstanding importance. Here, we report that five most clinically difficult‐to‐treat MDR Gram‐negative bacteria are highly sensitive to a synergistic combination of silver and ebselen. In contrast, silver has no synergistic toxicity with ebselen on mammalian cells. The silver and ebselen combination causes a rapid depletion of glutathione and inhibition of the thioredoxin system in bacteria. Silver ions were identified as strong inhibitors of Escherichia coli thioredoxin and thioredoxin reductase, which are required for ribonucleotide reductase and DNA synthesis and defense against oxidative stress. The bactericidal efficacy of silver and ebselen was further verified in the treatment of mild and acute MDR E. coli peritonitis in mice. These results demonstrate that thiol‐dependent redox systems in bacteria can be targeted in the design of new antibacterial drugs. The silver and ebselen combination offers a proof of concept in targeting essential bacterial systems and might be developed for novel efficient treatments against MDR Gram‐negative bacterial infections.